Challenges and support experienced by family caregivers seeking antiretroviral therapy services for children living with HIV/AIDS: a phenomenological study in Ghana - Najart Deborah Mumuni; Wahab Osman; Mavis Mallory Mwinbam; Margaret Wekem Kukeba; Lilian Yiryuo; Stephen Kpekura; Anthony Dery (BMJ Open, 2024)
Background Family caregivers of children living with HIV/AIDS in most cases are found to be overwhelmed and under-resourced, yet they are believed to be the primary source of support for children living with HIV/AIDS. Family caregivers experience different challenges that affect their children’s antiretroviral therapy (ART) adherence.Aim This study explored the lived experiences of family caregivers of children living with HIV/AIDS who sought ART services for these children at the St Joseph’s Hospital of Jirapa, Ghana.Method Using a qualitative phenomenology design and a semistructured in-depth interview guide and using purposive sampling, data were gathered from 13 family caregivers of children living with HIV/AIDS receiving ART treatment at St Joseph’s Hospital, Jirapa following ethical approval. All interviews were audio-taped and transcribed verbatim. Reflexive thematic analysis was used to analyse the transcribed data.Findings Six themes were generated: five challenges and one support. Family caregivers of children living with HIV/AIDS experienced: (1) Financial challenges, (2) Human-related challenges, (3) Challenges at HIV testing and counselling (HTC) centres, (4) Challenges with transportation, (5) Challenges in disclosing children’s HIV status to them and (6) Support received from HTC and their family members.Conclusion and recommendation Family caregivers of children living with HIV/AIDS experience daunting challenges in their quest to care for their children. Governmental and non-governmental HIV/AIDS programme support should include small business skills training and acquisition including capital to help set up small-scale businesses for such caregivers to reduce their financial challenges. Access to ART at clinics closer to caregivers is also key to promoting adherence. Family and community support has been recognised as key to enhancing ART adherence. Education of caregivers on policy regarding disclosure of the HIV/AIDS status of children, the need to work to reduce the time spent by caregivers at HTC, and ensuring privacy by limiting access to HTCs to only caregivers and their children, are important to enhancing adherence.